A near-infrared fluorogenic probe for nuclear thiophenol detection. Issue 22 (18th February 2021) - Niu, Jinye; Li, Yong; Zhang, Ran; Zhang, Jian; Wang, Xu; Xie, Xilei; Jiao, Xiaoyun; Tang, Bo
Abstract : Based on the thiolysis of dinitrophenyl ethers, a nucleus-targeted fluorescent probe, AQD, with bisalkylaminoanthraquinone as the fluorophore, was prepared for the near-infrared mapping of thiophenol in live cells, zebrafish, and mice. Abstract : Based on the thiolysis of dinitrophenyl ethers, a nucleus-targeted fluorescent probe, AQD, with bisalkylaminoanthraquinone as the fluorophore, was prepared for the near-infrared mapping of thiophenol in live cells, zebrafish, and mice.